2019
DOI: 10.1038/s41598-018-36496-9
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of calcium in an in vitro model of human breast tumour calcification reveals functional role for ALP activity, altered expression of osteogenic genes and dysregulation of the TRPM7 ion channel

Abstract: Microcalcifications are vital mammographic indicators contributing to the early detection of up to 50% of non-palpable tumours and may also be valuable as prognostic markers. However, the precise mechanism by which they form remains incompletely understood. Following development of an in vitro model using human breast cancer cells lines cultured with a combination of mineralisation-promoting reagents, analysis of calcium deposition, alkaline phosphatase (ALP) activity and changes in expression of key genes was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 69 publications
4
25
0
Order By: Relevance
“…This capacity of breast cells to develop osteomimetic properties were also reported in 2019 by O'Grady et al [103]. In fact, they demonstrated the ability of breast cancer cell lines to mineralize, and doing so, proved the capacity of breast cancer cells to produce de novo microcalcifications in osteogenic conditions [103]. Furthermore, microcalcifications are described as an indirect sign of pathological process, such as inflammation, and, as described previously, inflammation is also associated with breast involution in both post-lactation and peri-menopausal contexts, but also in tumorigenesis and tumoral growth.…”
Section: Sfrp1 and Microcalcificationssupporting
confidence: 75%
See 2 more Smart Citations
“…This capacity of breast cells to develop osteomimetic properties were also reported in 2019 by O'Grady et al [103]. In fact, they demonstrated the ability of breast cancer cell lines to mineralize, and doing so, proved the capacity of breast cancer cells to produce de novo microcalcifications in osteogenic conditions [103]. Furthermore, microcalcifications are described as an indirect sign of pathological process, such as inflammation, and, as described previously, inflammation is also associated with breast involution in both post-lactation and peri-menopausal contexts, but also in tumorigenesis and tumoral growth.…”
Section: Sfrp1 and Microcalcificationssupporting
confidence: 75%
“…Furthermore, they proved an osteoblast phenotype acquisition of the cells producing hydroxyapatite by performing immunohistochemical analysis. This capacity of breast cells to develop osteomimetic properties were also reported in 2019 by O'Grady et al [103]. In fact, they demonstrated the ability of breast cancer cell lines to mineralize, and doing so, proved the capacity of breast cancer cells to produce de novo microcalcifications in osteogenic conditions [103].…”
Section: Sfrp1 and Microcalcificationssupporting
confidence: 54%
See 1 more Smart Citation
“…In fact, O’Grady et al . showed that ALP enzyme activity was increased by OC in MDA-MB-231 and SKBR3 cells with calcium deposition 25 . However, the study did not completely unveil how breast cancer cells acquire ALP enzyme activity, although they showed that ALP inhibitor levamisole suppress mineralization in MDA-MB-231 cells cultured using OC.…”
Section: Discussionmentioning
confidence: 97%
“…A high expression of ALP in breast cancer has been reported. Mineralizing cell lines (MDA-MB-231 and SKBR3) displayed higher levels of ALP activity that was further increased by the addition of mineralization-promoting media [ 117 ]. Additionally, elevated levels of ALP in the serum of breast cancer patients were detected when compared to controls [ 118 ], in patients with bone metastases in comparison to patients without bone metastases [ 119 , 120 ], and also in advanced stages of breast cancer as compared to early stages and/or healthy controls [ 121 , 122 ].…”
Section: Cellular and Molecular Mechanisms For Calcification In Thmentioning
confidence: 99%